(untitled) (Fiep Bulletin - online, 2015)
The current study wishes to comprehend the “malha” game as one of the leisure choices to the elderly residents in the city of Miguel Pereira (RJ), describing the scenario which makes this game work and its peculiarities, making the reveal of the social characteristics that has intimate relationship with traditional cheerful and sports activities possible, facilitating the perception of the influence of those traditional activities in construction of the identity of small groups, considering that the moralistic principles from the cheerful and sports activities are not only from these activities, but from values that pass by society as a hole. The players of “malha” form small groups that have a common goal, e.g. the quarrel, the meetings and distraction, creating bonds in the participants that perpetuate the game as time goes. The ethnography appears in this study as an effective tool in the attempt to elucidate the questions that involves the game in the cited region. Herewith, during this article, answers shall arise and give clues of the importance of this activity in its players’ quotidian, making a sociability and leisure rising possible, and an occupation to the retired people who use the “malha” game as a powerful instrument for distraction. This seems to be an important period of life when there is a social removal due the segregation deriving from decrease of production power. It makes several elderly stress their diseases and/or develop others. Due to these worries, the physical education, the sport and leisure are now seen as important means to the upgrading of the quality of elderly lives. This may take government entities to develop activities to reach those aims through their public policies.